Evaluation and emotional consequences of the decision to postpone the Tokyo 2020 Olympic Games in Polish elite athletes - Nowak, M.; Pilchowska, I.; Domienik-Karlowicz, J.; Krysztofiak, H. (Studies in Sport Humanities, 2021)
In March 2020, because of the COVID-19 pandemic, the International Olympic Committee decided to cancel the Tokyo 2020 Olympic Games and postpone it to 2021. This decision caused a lot of emotions among elite athletes and disrupted their preparation cycle for the most important quadrennial athletic competition. The aim of the study was to investigate how Polish elite athletes regard this decision and what emotions they feel about it. The current training situation of athletes was also monitored during the study. 478 Polish elite athletes took part in the survey. The results showed that the athletes feel stronger sadness and uncertainty compared to the beginning of the year. Athletes with Olympic qualifi cation consider the decision to cancel the Olympic Games to be much more negative, but - what is interesting - is that they rate the current training options higher and declare feeling less concern about their sports form next year. Two independent clusters show that some athletes experience an increase in negative emotions, while others do not experience major changes (compared to the beginning of the year). Using factor analysis, two factors were also distinguished - emotional and sports. Both exhibited statistically signifi cantly correlations with opinions about the current training situation. The results obtained allow for the development of valuable recommendations regarding support for athletes. Strengthening the ability to regulate emotions, working with the structure of properly formulated goals and building awareness of maintaining a good attitude and approach will be particularly important.